2019
DOI: 10.3389/fmars.2019.00748
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Genypterus chilensis, a Commercial Benthic Marine Species of the South Pacific

Abstract: The red cusk-eel (Genypterus chilensis, Guichenot, 1848) is an iconic species in Chilean gastronomy, with a cultural significance that extends beyond its economic value, worthy of conservation. Despite the decline in fishery productivity across most of the distribution range for this species, little effort has been devoted to assessing stock management. In the present study, seven heterologous microsatellite loci (cmrGb3.8.1, cmrGb5.2B, cmrGb4.2A, cmrGb4.2B, cmrGb5.9, cmrGb4.11, and cmrGb2.6.1) were genotyped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…This species is abundant from southern Peru to the Chilean Patagonia (Vergara & George‐Nascimiento, 1982). Aspects associated with the farming of red conger eel have been studied in recent decades, including topics related to the development of farming technology, parasitism (George‐Nascimento et al., 2004), diet (Chong et al., 2006), the reproductive cycle (Chong & González, 2009) and genetic diversity and population structure (Córdova‐Alarcón et al., 2019; Jara‐Seguel et al., 2011). Particular focus has been given to the reproduction, growth, diet and genetics of red conger eels (Flores‐Kossack et al., 2020).…”
Section: Figurementioning
confidence: 99%
“…This species is abundant from southern Peru to the Chilean Patagonia (Vergara & George‐Nascimiento, 1982). Aspects associated with the farming of red conger eel have been studied in recent decades, including topics related to the development of farming technology, parasitism (George‐Nascimento et al., 2004), diet (Chong et al., 2006), the reproductive cycle (Chong & González, 2009) and genetic diversity and population structure (Córdova‐Alarcón et al., 2019; Jara‐Seguel et al., 2011). Particular focus has been given to the reproduction, growth, diet and genetics of red conger eels (Flores‐Kossack et al., 2020).…”
Section: Figurementioning
confidence: 99%
“…The results of the present study are consistent with those of Batista and Fabré (2001), who concluded that the coast of the Brazilian state of Maranhão is a part of the species' migratory circuit, which may exceed 300 nautical miles. Few physical barriers to dispersal exist in the ocean, and the dispersal of pelagic eggs and larvae on ocean currents, such as the Brazilian and North Brazil currents (see Rocha-Olivares et al, 2000;Broughton et al, 2002;Córdova-Alarcón et al, 2019), may also have contributed to the genetic homogeneity observed in the present study.…”
Section: Discussionmentioning
confidence: 81%
“…One reason for the divergence of the Cumana population may be its geographic location (Figure 1A), which is relatively isolated from the influence of adjacent marine environments, a situation that may limit its contact with other populations. Even so, fidelity to spawning sites, adaptations to specific oceanographic conditions, or feeding preferences may also be relevant here (Gold et al, 2010;López et al, 2010;Zhu et al, 2014;Córdova-Alarcón et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic divergence associated with low effective population sizes have been previously reported for other marine taxa, e.g. red cusk-eel Genypterus chilensis due to high fishing pressure (Cordova-Alarcon et al, 2019), and population bottlenecks for Gadus morhua (Andreev et al, 2015) and Epinephelus marginatus (Buchholz-Sorensen and Vella, 2016). The possible causes of low effective population sizes in CRN and PPC are not known.…”
Section: Genetic Structure and Connectivity In The Sulu Seamentioning
confidence: 94%